The Relationship between Trade Openness and Economic growth in Syria (the Causality and co-integration tests) (Journal of Hama University, 2021)
The relationship between trade openness and economic growth is ambiguous from boththeoretical and empirical point of view, while some theoretical assumptions reveal that trade openness leads to greater economic efficiency, market imperfections, and differences in technology may lead to a negative impact of trade openness on economic growth, especially in developing countries.Several studies have shown that the association of GDP growth with trade openness cannot be explained in many cases by the fact that the degree of openness has led to growth in output. Rather, the opposite may be true, as GDP growth may be a reason for trade openness, not a result of it, and vice versa.Therefore, this study attempts to research the relationship between trade Openness and economic growth in Syria.This study employed Granger causality to determine the direction of causality between trade openness and economic growth in the short run, while co-integration and the error correction model is (ECM) employed to determine the relationship between trade openness and economic growth in the long run. The study uses annual time series data from 1991 to 2017, obtained from the Central Bureau of StatisticsThe result of the Granger causality test shows that trade openness Granger causes economic growth, while economic growth doesn't, Granger causes trade Openness in the short run. The result of error correction model shows a unidirectional causality from trade openness to economic growth in the long run.Thus it can be concluded that changes in trade openness will have a significant effect on changes in the rate of growth in the short and long run.